Spherical Fuzzy Present Worth Analysis Method for Emergency Hospital Investment Analysis - Bolturk, Eda; Seker, Sukran (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2023)
As a subject of engineering economics, investment analysis plays an important role and use analysis techniques in the solution process. Present worth analysis, return of investment, and cost/benefit analysis are the most popular investment analysis techniques in engineering economics. However, since some investment values are determined by humans/experts and these values are based on human thoughts, it is very difficult to specify exact values. In this way, fuzzy logic can be a better alternative for calculating vagueness in engineering economics' applications. Thus, uncertain cash flows, indefinite life, and indefinite time value of money require to use fuzzy present worth analysis. As a new extension of fuzzy sets, spherical fuzzy sets have stronger capabilities to model uncertain information in investment analysis problems. In this article, spherical fuzzy present worth analysis method is presented for the first time to address the fuzzy parameters of public emergency hospital investment, which is currently a major subject in Turkey. The public emergency hospital for three locations on the European side of Istanbul is evaluated using spherical fuzzy present worth analysis method. While the best location for the emergency hospital is determined as Kemerburgaz, we also conduct a sensitivity and comparison analysis in order to show the robustness and applicability of the proposed method.
Keywords: Investment; Hospitals; Economics; Costs; Uncertainty; Fuzzy sets; Economic indicators; Engineering economics; hospital investment economic analysis; present worth analysis (PWA); spherical fuzzy sets (SFSs); COVID-19; SYSTEMS; Business & Economics; Engineering